EFEKTIVITAS MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTUAN MEDIA QUESTION CARD TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA KELAS IV SD - Ida Ayu Wayan Aprilia Cahyani; Ida Ermiana; Asri Fauzi (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2026)
Critical thinking is a logical thinking process in analyzing information, evaluating arguments, and solving problems systematically. One strategy to stimulate this ability is through the Problem-Based Learning (PBL) model, which directs students toward problem-solving. The effectiveness of the Problem-Based Learning model can be optimized through the use of Question Card media, which is an innovative and creative learning medium designed to trigger curiosity and active student involvement through engaging questions. This study aims to examine the effectiveness of the Problem-Based Learning model assisted by Question Card media on the critical thinking skills of fourth-grade students at SDN 11 Cakranegara. The research method used was a Non-equivalent Control Group Design. The subjects in this study were all fourth-grade students at SDN 11 Cakranegara, consisting of class IV A with 26 students as the experimental group and class IV B with 31 students as the control group. Data collection techniques used in this study were tests (essays) and observations. The data analysis technique began with prerequisite tests, namely the Kolmogorov-Smirnov normality test with a significance level of 5% (0.05), followed by the Levene’s test for homogeneity. Furthermore, the hypothesis was tested using the Independent Sample T-test. Based on the hypothesis testing at a 5% (0.05) significance level, the results showed t-count = 8.928, while t-table = 1.673, meaning t-count > t-table. The Sig. (2-tailed) value was 0.00, which is less than 0.05; therefore, the alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected. This indicates that the Problem Based Learning model assisted by Question Card media is effective toward the critical thinking skills of fourth-grade students at SDN 11 Cakranegara. ABSTRAK Berpikir kritis merupakan proses berpikir logis dalam menganalisis informasi, mengevaluasi argumen serta memecahkan masalah secara sistematis. Salah satu strategi untuk menstimulus kemampuan ini adalah melalui model pembelajaran Problem Based Learning (PBL), yang mengarahkan siswa pada pemecahan masalah. Efektifitas model pembelajaran Problem Based Learning dapat dioptimalkan melalui penggunaan media Question Card yang merupakan sebuah media pembelajaran yang inovatif dan kreatif yang dirancang untuk memicu rasa ingin tahu serta keterlibatan aktif siswa melalui pertanyaan yang menarik. Penelitian ini bertujuan untuk menguji efektivitas model Problem Based Learning berbantuan media Question Card terhadap kemampuan berpikir kritis siswa kelas IV SDN 11 Cakranegara. Motode penelitian yang digunakan adalah Non-equivalent Control Gruop Design. Subjek dalam penelitian ini adalah seluruh siswa kelas IV SDN 11 Cakranegara yang terdiri dari kelas IV A sejumlah 26 siswa mmenjadi kelas eksperimen dan kelas IV B sejumlah 31 siswa menjadi kelas kontrol. Teknik pengumpulan data yang digunakan dalam penelitian ini yaitu tes (uraian) dan observasi. Teknik análisis data diawali dengan uji prasyarat yaitu uji normalitas dengan uji Kolmogorov Smirnov dengan taraf signifikansi 5% (0,05) dan dilanjutkan dengan uji homogenitas dengan uji Levene tetst. Selanjutnya uji hipótesis pada taraf signifikansi 5% (0,05) diperoleh thitung=8,928, sedangjan t-tabel=1,673 sehingga t-hitung > t-tabel dan diperoleh nilai Sig.2 tailed=0,00 lebih kecil dari 0,05 maka hipótesis alternatif (Ha) diterima dan hipótesis nol (H0) ditolak. Artinya model pembelajaran Problem Based Learning Berbantuan Media Question Card efektif terhadap kemampuan berpikir kritis siswa kelas IV SDN 11 Cakranegara.